Expenditure patterns on foodservice in Malaysia - Tey, Yeong Sheng; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Abdullah, Amin Mahir; Radam, Alias (Penerbit Universiti Teknologi MARA (UiTM) Malaysia, 2010)
Rapid changes have occurred in the way food is prepared, in the way it is cooked, and in the places it is consumed. Foodservice has become increasingly important in the composition of the food account among Malaysians. The objective of this study is to analyze consumers’ expenditure pattern on foodservice in Malaysia. Several functional forms and a Heckman two-step methodology to account for censored-response bias are employed in the analysis of Household Expenditure Survey 2004/2005 data. Regardless of functional forms, the empirical estimates of income elasticity of demand for foodservice are significantly bigger than income elasticity of demand for food at home. This study shows positive prospect for foodservice industry in Malaysia, where an increase in income has the propensity to lead to an increase in expenditure (demand) on foodservice.